Evaluating the Relationship Between GPS Output and Planimetry System - Mohammad, A. R. A.; Hatim, A. J.; Sarsam, M.N.; Mohammed, K. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
. This rtsearch involveda a study of the relationship between GPS coordinates and planimetry coordinates. It was found that there is a relation between GPS output coordinates and the coordinates of a distance point from the positi on of the GPS point . In order to pricist the direction of distance a reference point had been used which is ( Greenwich Mean observatory) GMO. The angles between the studying points and Equator have al so been calculated Greenwich line. Also calculated the angle between every two regions have been calculated.